ANALYZING TIKTOK CONTENT MARKETING IN 2024 PRESIDENTIAL ELECTION ON GEN-Z IN MANADO - Korompis, Virginia; Tumbuan, Willem J. F. Alfa; Pandowo, Merinda Herrari Ch. (Universitas Sam Ratulangi, 2024)
This research aims to analyzing TikTok content marketing in the 2024 Presidential Election, focusing on Gen-Z in Manado. Using qualitative research methods, the study investigates how various content strategies impact voter engagement and decision-making. The findings reveal that effective content strategies, such as consistent posting frequency, engaging content styles, and meaningful user interaction, play pivotal roles in shaping audience engagement and perceptions. Follower growth serves as an important indicator of a candidate's popularity and credibility, yet it is not the sole determinant of voting decisions among Gen-Z. Engagement metrics like likes, shares, comments, and user interaction provide valuable insights into the effectiveness of the candidates' digital marketing efforts. Ultimately, successful TikTok content marketing requires a deep understanding of Gen-Z's preferences and behaviors, enabling candidates to create messages that resonate and influence this demographic. By utilizing these strategies, candidates can enhance their visibility and appeal, and potentially influencing the voting decisions of Gen-Z in Manado. Keyword: Content Marketing, Digital Marketing Strategies, Political Campaigns